The Role of Astrocytic Aquaporin-4 in Synaptic Plasticity and Learning and Memory - Szu, Jenny I.; Binder, Devin K. (Frontiers in Integrative Neuroscience, 2016)
Aquaporin-4 (AQP4) is the predominant water channel expressed by astrocytes in the central nervous system. AQP4 is widely expressed throughout the brain, especially at the blood-brain barrier where AQP4 is highly polarized to astrocytic foot processes in contact with blood vessels. The bidirectional water transport function of AQP4 suggests its role in cerebral water balance in the CNS. The regulation of AQP4 has been extensively investigated in various neuropathological conditions such as cerebral edema, epilepsy, and ischemia, however, the functional role of AQP4 in synaptic plasticity, learning, and memory is only beginning to be elucidated. In this review, we explore the current literature on AQP4 and its influence on LTP and LTD in the hippocampus as well as the potential relationship between AQP4 in learning and memory. We begin by discussing recent in vitro and in vivo studies using AQP4 knockout (KO) and wild-type mice, in particular, the impairment of LTP and LTD observed in the hippocampus. Early evidence using AQP4 KO mice have suggested that impaired LTP and LTD is BDNF dependent. Others have indicated a possible link between defective LTP and the downregulation of glutamate transporter-1 which is rescued by chronic treatment of β-lactam antibiotic ceftriaxone. Furthermore, behavioral studies may shed some light into the functional role of AQP4 in learning and memory. AQP4 KO mice performances utilizing Morris water maze, object placement tests, and contextual fear conditioning proposed a specific role of AQP4 in memory consolidation. All together, these studies highlight the potential influence AQP4 may have on long term synaptic plasticity and memory.